CURRENT PROBLEMS OF ROAD TRUCK TRANSPORT PERFORMANCE AND SAFETY (Perner's Contacts, 2023)
Although the economic development of the Czech Republic in the past decade can be assessed as entirely positive, the development of the performance of domestic road freight carriers showed a sharp decline during the same period. However, European road truck transport was forced to solve an extensive range of problems, which had a noticeable impact on domestic carriers. The presented paper aims to find and indicate the causes of this development and point out some factors that helped to reverse the unfavorable development.
Keywords: road truck transport; digital consignment note; phantom transport; cross-border trade